A novel expander-depending natural gas pressure regulation configuration: Performance analysis. (15th June 2018) - Xiong, Yaxuan; An, Shuo; Xu, Peng; Ding, Yulong; Li, Chuan; Zhang, Qunli; Chen, Hongbing
Highlights: A novel system which can recover pressure energy as well as regulate pressure is proposed. Round trip efficiency of the whole system (including gas source) reaches up to 25%. Isentropic efficiency of expander has great influence on round trip efficiency. Wide installation of the system bring about rich economic and environmental benefit. Abstract: Natural gas (NG) is delivered with abundant pressure energy from the gas station to various industrial users and residents. The commonly used Throttle Valve Pressure Regulation configuration can achieve stable downstream pressure, but the gas pressure loss is great. Additional turbines could be employed to recover the pressure energy, but hard to present a high efficiency. This work innovatively proposes an Expander-Depending Natural Gas Pressure Regulation configuration, which can regulate the NG pressure and harvest the pressure energy as well. A single screw expander is used to recover the pressure energy, whereby an air-source heat pump acts as a heat source to warm the cold gas. A thermodynamic model is established to evaluate the energy and exergy performance. Thermodynamic analyses show that the daily round-trip efficiency of the system, including both the NG source sector and the expander-depending NG pressure regulation sectors, can be more than 25% while the daily exergy efficiency and the daily power output of the expander-depending gas pressure regulation sector come up to 37.02% and 60.9 kWh respectively under the inlet NG pressure of 0.6 MPa and the outlet NG pressure of 0.1 MPa, and the volume flow rate from 30 Nm 3 /h to 350 Nm 3 /h. The round-trip efficiency, the exergy efficiency and the net power output dramatically increase with the isentropic efficiency improvement of the single screw expander. The proposed expander-depending natural gas pressure regulation unit can produce rich economic and environmental benefits and promise a bright future in the engineering application.